First‐in‐human intracochlear application of human stromal cell‐derived extracellular vesicles. Issue 8 (4th June 2021) - Warnecke, Athanasia; Prenzler, Nils; Harre, Jennifer; Köhl, Ulrike; Gärtner, Lutz; Lenarz, Thomas; Laner‐Plamberger, Sandra; Wietzorrek, Georg; Staecker, Hinrich; Lassacher, Teresa; Hollerweger, Julia; Gimona, Mario; et al.
Abstract: Extracellular vesicles (EVs) derived from the secretome of human mesenchymal stromal cells (MSC) contain numerous factors that are known to exert anti‐inflammatory effects. MSC‐EVs may serve as promising cell‐based therapeutics for the inner ear to attenuate inflammation‐based side effects from cochlear implantation which represents an unmet clinical need. In an individual treatment performed on a 'named patient basis', we intraoperatively applied allogeneic umbilical cord‐derived MSC‐EVs (UC‐MSC‐EVs) produced according to good manufacturing practice. A 55‐year‐old patient suffering from Menière's disease was treated with intracochlear delivery of EVs prior to the insertion of a cochlear implant. This first‐in‐human use of UC‐MSC‐EVs demonstrates the feasibility of this novel adjuvant therapeutic approach. The safety and efficacy of intracochlear EV‐application to attenuate side effects of cochlea implants have to be determined in controlled clinical trials.